Computation of Calcium Score With Dual-Energy Computed Tomography: A Phantom Study. Issue 1 (January 2017) - Kumar, Vidhya; Min, James K.; He, Xin; Raman, Subha V.
Abstract : Abstract: Dual-energy computed tomography (DECT) improves material and tissue characterization compared with single-energy CT; we sought to validate coronary calcium quantification in advancing cardiovascular DECT. In an anthropomorphic phantom, agreement between measurements was excellent, and Bland-Altman analysis demonstrated minimal bias. Compared with the known calcium mass for each phantom, calcium mass by DECT was highly accurate. Noncontrast DECT yields accurate calcium measures and warrants consideration in cardiac protocols for additional tissue characterizations.